Public Housing in Medan during the Dutch Colonial Period - Suprayitno; Wara Sinuhaji; Deo Widika Alamsyah (Budapest International Research and Critics University, 2020)
As the center of government and economy in the East Sumatra region during the Dutch colonial era, the city of Medan continued to develop and grow in line with the success of the surrounding plantation businesses. This situation resulted in many people coming to Medan to stay and settle down. The large number of people who came to Medan resulted in an increase in population in Medan which resulted in an increase in the number of housing needs at that time, especially houses that met health and safety standards. Since there were many houses that did not meet the standards at that time, the Medan City Government considered that this housing problem had to be taken seriously so they made a policy to establish public housing that met the standards set, which was called “Volkshuisvesting” or people's houses. This housing development policy was also widely carried out in several Gemeente in the Dutch East Indies at that time. Volkshuisvesting itself is public housing aimed at middle and low income people with the aim of helping them to have a decent place to live in. Many things have been prepared by the Medan City government to realize this public housing policy for the people or Volkshuisvesting, starting from planning, provision of funds, housing areas etc. Using historical methods and using sources such as the Dutch colonial archives, newspapers and books that discuss housing published during the Dutch colonial period, this article explains how the Medan City Government plans to build public housing in Medan.